An activist-holiness Kenneth Hagin? A case study of prosperity theology in the Philippines - Maltese, Giovanni (Peter Lang AG, 2015)
Abstract Prosperity theology and holiness theology are frequently regarded as irreconcilable antitheses in Pentecostal Studies and both as opposed to "structural" approaches to poverty alleviation.2 This is different in Dumaguete Philippines. Here, prosperity theology is holiness theology and it is oftentimes framed along issues that relate to the Filipino nation and society. Analyzing articulations on prosperity, this chapter will show how causes and solutions for poverty are debated among pastors and how they lead to different practices. Drawing on extensive field work (2009-2014) I argue that holiness theology became a means of rationalization vis-à-vis the failures of prosperity teachings to deliver on its prom ises. Providing a language for articulating moral critique of both, individuals and social con ditions as a whole, it leads to an alternative explanation for the failures of development in terms that include collective and structural sin. Accordingly, the confession and seed-faith principles, inherited from the Word-of-Faith-Movement are turned collective, which leads to different forms of social and political engagement as remedy for poverty.
CRIS-Team Scopus Importer:2024-03-27

Gender and the Conceptualization of Religion and Islam - Maltese, Giovanni (Implicit Religion, 2023)
The critique of power asymmetries reproduced by Eurocentric and essentialist conceptualizations of generic terms and analytical concepts is well-established in religious studies and gender studies, especially when investigating Islam. Yet each discipline is in danger of omitting the most critical discussions of the other. Discussions about conceptualizations of religion and Islam, even those adapting theoretically sophisticated global history approaches, largely ignore gender. Scholars of gender studies, in turn, have barely queried or nuanced “religion” and “Islam” as categories. Thus, they fail to take into account how conceptualizations of religion and Islam as generic terms have affected the power relations under scrutiny. This article aims to address this momentous mutual exclusion by examining a tract published in 1940 in the context of Anglophone Southeast and South Asian Muslim intellectual circles. Drawing on Judith Butler’s critical engagement with Luce Irigaray and on Butler’s notion of subversion by thoroughgoing appropriation and redeployment and situating this case study within the mentioned mutual exclusion, I argue that studying the relation between concepts of femininity and masculinity and concepts of religion and Islam poses important questions regarding colonial, androcentric, and phallogocentric epistemologies underlying contemporary religious studies and gender studies. I contend that religion-making and gender-making should not be investigated apart from each other.
CRIS-Team Scopus Importer:2024-03-27
Keywords: 1930s/40s South and Southeast Asia; feminism; gender studies; Global Religious History; Islam and gender; masculinity/femininity

Global religious history - Maltese, Giovanni; Strube, Julian (Method and Theory in the Study of Religion, 2021)
Understandings of religion have been fundamentally transformed since the nineteenth century. The respective contradictions, ambiguities, continuities, and ruptures can be most comprehensively grasped when viewed against the background of global entanglements. For this purpose, the approach of global religious history proposes a range of theoretical and methodological tools. Its theoretical repertoire is largely informed by a critical engagement with poststructuralist epistemology and postcolonial perspectives embedded in a consistent genealogical approach. At the outset, it aims at bridging divisions, including those between postcolonial and global history, between disciplines such as religious studies and history, as well as between different area studies. This implies a theoretically robust reflexion of the question of what global entanglements mean in global religious history, along with the question of how to distinguish global religious history from approaches usually qualified by the prefix trans as, for example, in "transregional." In this introduction, we offer an in-depth discussion of the theoretical foundations and methodological implications of global religious history.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Entanglement; Genealogy; Global history; Modernity; Postcolonialism; Poststructuralism

Islam is not a "religion"-global religious history and early twentieth-century debates in British Malaya - Maltese, Giovanni (Method and Theory in the Study of Religion, 2021)
Lately, Islamicists have called to discard "religion" as a conceptual tool and/or to use the "Qur.anic term" din instead, arguing that "religion" entails Eurocentric bias. Analyzing how Fazl-ur-Rahman Ansari conceptualized Islam and religion in the late 1930s and early 1940s, this article presents a threefold argument. Firstly, I argue that a global history approach which examines in a poststructuralist framework how "Islam" and "religion" are used in concrete contexts is better suited to address the problem of Eurocentrism in both Religious Studies and Islamic Studies. Secondly, I challenge the scholarly thesis that twentieth-century Southeast Asian intellectual debates which referred to Islam as religion were mere emulators of debates conducted in the "West." Instead of assuming isolated histories and ignoring Southeast Asian debates, I contend that the current use of and debates about conceptualizations of Islam as/and religion are the product of one and the same discourse-a result of global negotiation processes in which Europeans were as involved as Southeast Asia-based non-Europeans, even if they did not speak from the same position of power. Finally, I submit that the approach of global religious history opens new perspectives on contemporary Malaysian politics.
CRIS-Team Scopus Importer:2024-03-27
Keywords: British Malaya; Eurocentrism; Fazl-ur-Rahman Ansari; Islam; Malaysia; Shahab Ahmad

Negotiating evangelicalism and pentecostalism: Global entanglements, identity politics and the future of pentecostal studies - Maltese, Giovanni; Bachmann, Judith; Rakow, Katja (PentecoStudies, 2019)
Pentecostal studies seems to be caught in a deadlock with regard to its subject matter of research. Most definitions of Pentecostalism appear either too broad or too narrow compared with the inclusive sense in which “Pentecostalism” is used in academia. Scholars admit that Pentecostal is a “fuzzy category”, but still, they opt for a combination of essentialist definitions, rarely investigating whether their empirical data could open up fresh perspectives on how to conceptualize the subject matter of Pentecostal studies. Others postulate a “Pentecostalization” of Christianity and/or tend to dissolve Pentecostal studies into the study of Evangelicalism and/or Catholicism for other reasons. Still others prefer to speak of Pentecostalisms in the plural or seem to have given up on finding a consensus. The introduction to this special issue proposes an alternative approach. Drawing on Michael Bergunder's work, it suggests to conceptualize Pentecostalism as a name that keeps together various equivalential chains. As the articles collected in this special issues show, this means to investigate the meaning “Pentecostalism” assumes in specific research contexts as product of local identity politics and analyse its entanglement in a global discourse about “Pentecostalism”.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Antagonism; Discourse; Equivalential chains; Evangelicalism; Global entanglements; Hegemony; Identity politics; Knowledge production; Local negotiations; Pentecostal studies

Phallogocentrism, Global Entanglements and Comparison in the Study of Religion Mysticism and Gender as Category of Knowledge among Muslim Intellectuals (1938–41) - Maltese, Giovanni (Interdisciplinary Journal for Religion and Transformation in Contemporary Society, 2023)
Along with the critique of generic terms, such as religion or mysticism, regarded as Western-centric, comparison in religious studies has been faulted for reinforcing Western dominance over the rest of the world. Global Religious History claims to constructively address these charges by focusing on global entanglements. On closer inspection, however, if the latter are theorized at all, an astounding exclusion comes to the fore: the omission of gender as category of knowledge. Engaging this phallogocentrism in Global Religious History, this article calls for a conceptualization of global entanglements that takes this omission seriously. As a case study, I use a tract published serially in a Singapore-based Islamic missionary journal (1938–1941), to argue that a revised conceptualization of global entanglements can help to uncover the contributions of non-hegemonic subjects to contemporary discourses on religion, mysticism, Islam, and Sufism, as well as to the comparative study of religion.
CRIS-Team Scopus Importer:2024-03-27
Keywords: 1930s/40s; Gender; Islam; Mysticism; Phallogocentrism; South and Southeast Asia; Sufism

Reproductive politics and populism: Pentecostal religion and hegemony in the Philippines - Maltese, Giovanni (The Journal of Law and Religion, 2019)
Reproductive politics is the locus classicus for studying the entanglement of religion with politics and lawmaking processes in the Philippines. Although 25 percent of the total population participates in the Pentecostal movement, there is virtually no comprehensive work that studies this movement's attitudes about reproductive health. In this article I analyze Pentecostals' attitude on reproductive health vis-à-vis recent studies that depict the movement as religious populism. I investigate the interests and exclusions that Pentecostals' keywords and narratives, as well as recent scholarship on Pentecostalism, conceal. I first provide a genealogical reconstruction of the debate on reproductive health in the Philippines. Second, I provide an overview of the religious landscape and discuss Pentecostal's attitudes toward reproductive health while demonstrating that their rhetorical positions cannot be understood apart from hegemonic struggles and their entanglement with local and global discourse. Third, I draw theoretical and methodological implications for the study of Pentecostalism, politics, and lawmaking processes in the Philippines. Finally, I conclude by showing the relationship between Pentecostalism in the Philippines and the broader study of religion and politics, including making and implementing law.
CRIS-Team Scopus Importer:2024-03-27
Keywords: hegemony; Pentecostalism; Philippines; populism; reproductive politics

Spiritual Warfare and Right-Wing Authoritarianism - Maltese, Giovanni (Implicit Religion, 2021)
This article focuses on contemporary spiritual warfare discourse and on the apparent affinity to right-wing authoritarianism of Christians related to it. Drawing on material from the Philippines, I investigate the role of scholarship in fostering said affinity by reading Christians, who seem to be connected to the spiritual warfare discourse, through the lens of prominent U.S.-American dominionists. I argue that the approach of global religious history helps to critique the Anglo-Eurocentric and elitist biases underlying current research about Christianity in the majority world.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Donald Trump; global Christianity; Jair Bolsonaro; Philippines; right-wing authoritarianism; Rodrigo Duterte; spiritual warfare